Aflasafe BF01 for Burkina Faso - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In 2019, an additional distribution partner, SAPHYTO SA, was appointed to distribute Aflasafe BF01 for use in maize and groundnut. Elephant Vert was the first distribution partner in Burkina Faso in 2018.